Strategi Promosi Agen Properti Independen Pada Media Online - Fitria, Yuyun; Farida, Farida (Jurnal Komunikasi Profesional, 2018)
The development of online media is now a powerful weapon to help promote. It is the sophistication of various online media features that are utilized by independent property agents to be able to compete with other agents and carry out the best promotional strategies. This study aims to find out an overview of the promotional strategies used by independent property agents on online media. This study uses qualitative research methods with the type of analysis research. The results showed that the two subjects had online media accounts each with different advertising characteristics, but from several online media used according to the most effective subject in property promotion was using rumah123.com and then OLX.Keywords:Promotion Strategy, Independent Property Agent, and Online Media